CREATION OF DYNAMIC ELECTRICITY DIGITAL TEACHING MEDIA BASED ON PROBLEM SOLVING LEARNING MODEL TO FACILITATE STUDENTS' PHYSICS PROBLEM-SOLVING SKILLS - Oktavia, Diah (Universitas Negeri Padang, 2024)
The problem encountered in the field is the lack of digital teaching media based on the problem solving learning model that can facilitate problem-solving skills. The difficulty of understanding the concept of physics in dynamic electrical materials has an impact on the low ability of students to solve Physics problems. In addition, the application of the learning model in schools has also not been able to facilitate students' problem-solving skills. Thus, the purpose of this research is to create a dynamic electrical digital teaching media based on the Problem Solving learning model to facilitate students' valid and practical physics problem-solving skills. This type of research is research and development with a 4D development model consisting of define, design, develop, and disseminate. Research is limited to the development stage. Research data is data for the analysis of needs, validity, and practicality. The data obtained were analyzed using Aiken's V formula for validity and the likert scale for practicality. The results of the study showed that the dynamic electricity digital teaching media based on the problem solving learning model was valid with an average score of Aiken's V ≥ 0.6. The values of the feasibility of content, linguistics, presentation, and graphichal components were 0.72, 0.72, 0.74, and 0.70, respectively. This media is also declared practical with a percentage of more than 60%. The students' responses to each assessment indicator were average 85.8%, 90.2%, and 87.4% with very practical criteria. The teachers' responses showed an average of 98.6%, 95.8%, and 97.5% with very practical criteria.Keywords :Student’s Problem Solving Ability, Media, Problem Solving